Electrochemical deposition of polypyrrole for symmetric supercapacitors - Muthulakshmi, B.; Kalpana, D.; Pitchumani, S.; Renganathan, N.G.
Composite electrodes for supercapacitors were prepared via electrochemical polymerization onto activated carbon. The capacitance properties were investigated using cyclic voltammetry (CV), AC impedance spectroscopy and charge-discharge tests. These electrodes show a specific capacitance of about 354 F g-1. This indicates that the in situ electro-polymerization of pyrrole onto carbon could improve the performance of carbon electrodes for use in supercapacitors.
Keywords: SUPERCAPACITORS; CONDUCTING POLYMERS; POLYPYRROLE; ACTIVATED CARBON; CYCLIC VOLTAMMETRY; SYMMETRIC CAPACITOR